A Study on Integration of 1kW PEM Fuel Cell into a Smart Microgrid System with Programmable Scenario. (2017) - Haq, Muhamad Maulanal; Haq, Irsyad Nashirul; Leksono, Edi; Tapran, Nugraha
Abstract: Hybrid Renewable Energy System (SHET) is a smart microgrid system that has been implemented in Energy Management Laboratory – ITB. The SHET consists of photovoltaic power plant, national electricity grid, battery based energy storage system and hybrid energy controller system. This SHET is operated to supply electricity to the laboratory. In this paper, 1 KW Proton Exchange Membrane Fuel Cell (PEMFC) integrated to the microgrid system is investigated. The PEMFC fuel cell is connected to the SHET through DC coupling method as one input for the hybrid energy controller. To optimize the energy conversion of the PEMFC and also to stabilize the input voltage to the hybrid energy controller, Maximum Power Point Tracker (MPPT) is used. This MPPT also functions as DC-DC converter. In this microgrid system where the PEMFC is also incorporated, the PEMFC will only supply its generated electricity whenever the system is in island mode with additional configured specific conditions such as battery's State of Charge (SoC) is lower than 40% or electricity load of the microgrid system is more than 0.72kW. The result of study showed that the PEMFC only generated 120-160W from its potential maximum power of 1kW. This happened because the battery voltage closes to the PEMFC Open Circuit Voltage (OCV) so the MPPT cannot operate the PEMFC to its Maximum Power Point. The low electrical power is supplied to system makes the battery still on discharge when the electricity load is in high level. This means, the PEMFC and battery work simultaneously at the same time. From this research, it has been found out that other solutions may be implement to maximize the generated power from the PEMFC